Literacy and Identities in Teacher’s Education Research in Brazil - Kleiman, Angela B. (Íkala, Revista de Lenguaje y Cultura, 2019)
This paper intends to account for several criteria and principles guiding the cre-ation of research programs carried out in Brazil from 1991 on, by researchers in the field of applied linguistics in the literacy studies approach. This approach aimed to help transform out-of-date and elitist structures in Education (like, for example, language curricula at Brazilian higher education). One of those pioneering groups was Letramento do Professor, which applied Street’s new para-digm (1984). This review also looks at new studies that gradually began adhering to the sociocultural and historic trend of literacy studies. Our main source of information to access those works was Lattes Brazil’s Research Group Directory, an agency under the umbrella of the National Research Council (cnpq), which has 512 research groups registered, which are doing or have done research on literacy. In line with the varied research subjects in literacy studies, namely rela-tions between literacy and power, effects of representations on written language among the most vulnerable social groups, in different settings, the theoretical grounds of those research works are examined here, including interactionist the-ories of language, cultural studies, decolonial theories, and literacy studies, with methodological approaches gathering together varied interpretative practices.